The Effect of Discipline and Work Environment on Employee Performance in Pelanja Sejahtera - Suci Rahayu Kartini; Cecep Haryoto (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of Discipline and Work Environment on Employee Performance at PT. Laksana Sejahtera. The study uses a quantitative method with an associative approach, using primary data obtained from 60 employees of PT. Laksana Sejahtera. The independent variables in this study are Discipline and Work Environment, while the dependent variable is Employee Performance. The results of the study indicate that, partially, Discipline has a significant influence on Employee Performance with a t- t-count value of 3.053 greater than the t-table (1.672) and a significance value of 0.003 <0.05. The Work Environment also partially has a significant influence on Employee Performance, with a t-count value of 5.631 greater than the t table and a significance value of 0.000 <0.05. Simultaneously, Discipline and Work Environment together have a significant effect on Employee Performance, as evidenced by the F-count value of 23 greater than the F table and a significance value of 0.000 <0.05. This indicates that both Discipline and Work Environment are important factors in improving Employee Performance at PT. Laksana Sejahtera.